Identifikasi Bumbu Bali di Beberapa Desa di Bali Selatan - Martadjaya, I Gusti Made Iwan Dusanta; Sudiarta, Ngakan Putu; Suprastayasa, I Gusti Ngurah Agung; Hardina (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Local cuisine is an important part of a region's cultural identity and has great potential as a tourist attraction. Balinese cuisine is known for its diversity and distinctive taste, which is influenced by the use of various types of traditional spices (basa). This study aims to identify the ingredients, composition, and manufacturing process of Balinese spices used in several villages in South Bali. Through a qualitative approach with observation, interviews, and documentation in four villages, it was found that there were significant differences in the use and composition of spices between regions. Some of the dominant types of spices are basa gede, basa selem, basa bawang jahe, sambel emba, sambel nyuh, basa uyah sere, and basa suna cekuh. This diversity reflects the richness of Balinese culinary culture and shows the importance of preserving traditional techniques and knowledge in making spices. These findings are expected to provide practical contributions to the development of local cuisine and support the promotion of Balinese gastronomic tourism